Didactic strategies to increase reading comprehension to 7-year-old students at academia naval altamar - Cajamarca Ruiz, Andrea Estefanía (2017)
The main purpose of this study is to determine the didactic strategies to increase the reading comprehension to 7-year-old students at Academia Naval Altamar. The information for this research were gathered through an investigation of several didactic strategies choosing the ones for those students……